Guia de orientação à prática de exercício físico em espaços públicos para pessoas idosas - Souto, Hugo Costa (2019)
Introduction: Populational aging occurs in the whole world and leads to morphological, functional, psychological, and social modifications which results in the reduction of functional capacity. The practice of moderate and regular physical activity contributes to preserve functional capacity, physical and mental well-being, and increase social contact, this way; it is of a fundamental importance the participation of the physical educator for functional stimulation, through the elaboration of an orientation guide for the practice of physical exercise. Objectives: to analyze the scientific production on physical activity for elderly people performed in public places in online journals from 2008 to 2018; to know the profile and difficulties reported by elderly people that perform physical activity in public places; and elaborate an orientation guide for the practice of physical exercise by elderly in public places. Methodology: It is a methodological research, of quantitative approach, structured in the following phases: integrative review of literature on the practice of physical activity performed in public places by these elderly people; exploratory study with quantitative approach of data, that used a sample of 30 elderly people that responded a semi structured questionnaire with questions about the realization of physical exercise in public places and the difficulties presented for their realization. And after the elaboration of a guide to orient the practice of physical activity by elderly in public places. Data were analyzed by descriptive and inferential statistics. Results and discussion: there was a predominance of female elderly (53,3%), married (53,3%), residing in own house (83,3%), living with partner (30%). Regarding individual income, 50% of elderly declared between 2 and 3 minimum wage. Concerning the referred morbidities, hypertension was the most reported (50%), followed by diabetes (20%), osteoporosis (15%), problems on vertebral column (10%) and cardiovascular problems (5%). Regarding use of medication, 60% of elderly utilize from two to three medicines. There is predominance of 43,3% of elderly that do physical activity in public places from to three times a week, with duration from 30 to 60 minutes (63,3%) for more than six months(76,7%). In relation to the structure of physical space, most of them (40%) of elderly consider that the infrastructure of parks in which they do physical activity as good and with good security (53,3%), however, with bad equipment maintenance (60%). In what refers to the difficulty to do physical activity in public places, there was predominance of lack of professional orientation, reported by 70% of elderly. Conclusions: It was possible to observe many benefits for elderly related to the practice of regular physical activity and some difficulties faced by them to do this. The elderly people are motivated to do physical activity in search of improvement in their quality of life, however, despite of good infrastructure of public parks, they don’t have maintenance on their equipment and there is a lack of orientation to do the exercises in a correct way in the equipments of the parks, thereby highlighting the importance of a technological product that aims to contribute to improve autonomy and security in the performance of physical exercise and quality of life of elderly people.